Synthesis, Characterization and Biological Studies of Organotin(IV) Carboxylates - Sonika; Nidhi; Malhotra, Rajesh (Asian Journal of Chemistry, 2010)
Organotin(IV) carboxylate of the type R2SnCl(LI), R2Sn(LII)2 (where, R = Ph, Bu; L = 1- naphthoxyacetate, 2-naphthoxyacetate) have been synthesized by the reaction of dichlorodiorganotin(IV) with sodium salt of ligand in 1:1 and 1:2 molar ratio. All the complexes have been characterized by spectral studies (IR, 1H, 13C and 119Sn NMR) and elemental analysis. On the basis of these studies, it was observed that the ligands behaved as bidentate coordinating through carboxylate oxygen atom. The ligands and carboxylate complexes were evaluated for in vitro antimicrobial activity against fungi Aspergillus niger, Candida albicans and against bacteria gram negative Escherichia coli and gram positive Staphylococcus aureus. The organotin(IV) carboxylate complexes were found to be more potent than the parent ligands.